2022
DOI: 10.1001/jamanetworkopen.2022.10552
|View full text |Cite
|
Sign up to set email alerts
|

Derivation and Validation of a Score for Predicting Poor Neurocognitive Outcomes in Acute Carbon Monoxide Poisoning

Abstract: Key Points Question Can a novel clinical scoring system predict poor neurocognitive outcomes after acute carbon monoxide poisoning? Findings This prognostic study developed and externally validated a prediction model including 5 risk factors associated with poor neurocognitive outcome at 1 month, creatine kinase level, hyperbaric oxygen therapy, Glasgow Coma Scale score, age, and shock (COGAS score), among patients with carbon monoxide poisoning. COGAS scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…It only analyzed factors that may be related to severe poisoning. A study of CO poisoning in patients aged 16 or older 17 showed that the main endpoint outcome was neurocognitive sequelae in the subsequent 4 A retrospective study from Taiwan on children showed that acute seizures, severe metabolic acidosis, signi cantly low blood pressure, prolonged unconsciousness, and longer hospitalization time were associated with delayed neurological sequelae (DNS) 5 . A total of 30 children were included in the study, and only 5 (16.7%) children developed delayed neurological sequelae, but all recovered completely within 2 months.…”
Section: The Severity Of Carbon Monoxide Poisoningmentioning
confidence: 99%
“…It only analyzed factors that may be related to severe poisoning. A study of CO poisoning in patients aged 16 or older 17 showed that the main endpoint outcome was neurocognitive sequelae in the subsequent 4 A retrospective study from Taiwan on children showed that acute seizures, severe metabolic acidosis, signi cantly low blood pressure, prolonged unconsciousness, and longer hospitalization time were associated with delayed neurological sequelae (DNS) 5 . A total of 30 children were included in the study, and only 5 (16.7%) children developed delayed neurological sequelae, but all recovered completely within 2 months.…”
Section: The Severity Of Carbon Monoxide Poisoningmentioning
confidence: 99%